Analytical approach for a better control of environmental contamination. (30th September 2020) - Bosco, R; Gambelli, S; Urbano, V; Cevenini, G; Messina, G
Abstract: Background: The environment of hospital rooms plays a role on Hospital Acquired Infections. Objects may be repository of germs and have a role on cross contamination, mainly in high-touch surfaces. Proper sanitation and disinfection procedures are needed. Aims: i) to highlight the different probabilities of microbial contaminations in Hospital, ii) to assess whether the use of a UVC device (UVC-D), after standard disinfection procedures, improves the level of hygiene. Methods: Between November 2019 and February 2020 a cross sectional study in a real clinical context was conducted. Investigations were carried out in double rehabilitation rooms with patients admitted for at least 48h. 16 preliminary Petri dishes (PD) were used in one rehabilitation room and bathroom, to assess the contamination level after deep disinfection procedures (T0). Matched comparisons were made after the use of UVC-D, 3 points/room and 1 point/bathroom, 3 minutes each(T1). At T0 we estimated the probability of contamination to select the following sampling. Six rooms and bathrooms were investigated using randomized spots. PD were incubated at 36 °C and colony forming unit (CFU) counted at 48h. Descriptive statistic and Wilcoxon test were performed to assess the levels of contamination between (T0) and (T1). Results: At T0 we have a mean of 5.83 CFU/PD (CI 3.79-7.86) and a median of 1.0 CFU/PD (min 0 - max 118); at T1 mean is 0.28 CFU/PD (CI 0.15-0.40) and median of 0 CFU/PD (min 0-max 5). Significant reduction of contamination was achieved between T0 and T1 (p < 0.001). 83, 33% of the contamination sites had 0 CFU/PD after using UVC-D. Conclusions: The probability approach has driven the selection of the highest contaminations spots. Standard disinfection, followed by using UVC-D, significantly reduces contamination assuring a lower probability of cross contamination and risk of infection. Key messages: Analytical approach to assess the contamination level of room to address with greater precision the points with higher risk of cross contamination. The UVC technology assures better results when associated with standard sanitation procedure decreasing the risk of hospital acquired infections.